Growth of Ocotea cernua (Lauraceae) in Peruvian Amazon floodplain forests - Baluarte Vásquez, Juan Rommel (2018)
Ocotea cernua (Nees) Mez "moena negra" is a commercial species that thrives in alluvial floodplain forests in the Peruvian Amazon. This study presents information about diameter growth of O. cernua and provides useful information for its forest management. The stand density and structure was analysed in nine permanent sample plots (100 m x 100 m) and 24 transects (40 m x 100 m). Analysis of tree diameters at different time indicates maximum values of 9.5 and 17.4 mm/year for the average annual diameter increment and the maximum annual diameter increment respectively; both into 25 ‒ 30 cm diameter classes. Considering this increments, a tree will reach a diameter higher than 30 cm DAP, in 60 to 34 years respectively. Estimations of the adjusted model showed the maximum annual growth increment estimated in 2.10, 1.28 and 0.50 cm for trees with low, medium and high competition, corresponding to trees with DBHs of 21.10, 20.28 and 20.50 cm for trees with low, medium and high competition, respectively. However, the time required to reach such diameters is highly variable with values of 12.31, 20.35 and 54.51 years, respectively.